Realization of a novel multimode waveguide with photonic band gap hopping based on coupled-resonator optical waveguide theory - Yonghui Zheng; Chang Wang; Zhiyong Tan; Zhenzhen Zhang; Jun Jiang; Binbin Cheng; Juncheng Cao (Results in Physics, 2023)
Traditionally, in the application of photonic crystals, defect modes are mostly introduced in the photonic band gap to realize high-performance waveguides, and electromagnetic waves beyond the photonic band gap cannot be controlled in photonic crystals. Here we demonstrated a kind of deep subwavelength quasi-photonic crystal waveguide, named 2D closed surface-wave photonic crystal, by combining a photonic crystal with a spoof surface plasmon polaritons-based metal–insulator–metal structure. The closed surface-wave photonic crystal waveguide can realize the introduction of the defect mode in the frequency band where the first-order dispersion curve of the surface-wave photonic crystals is located, instead of being limited to the frequency range of the photonic band gap of surface-wave photonic crystals. At the same time, we confirmed the correctness of the coupled-resonator optical waveguide theory under the conditions of the first-order mode and the multi-order mode based on the closed surface-wave photonic crystal guided-wave mechanism. We have verified our work in 80–130 GHz through experiments, theory, and simulation, which are consistent. The closed surface-wave photonic crystals can be used as a kind of highly integrated waveguide and multi-bandpass/band-elimination filter in integrated optical circuits, and can adjust the working frequency band at very low cost.